Just Follow the Yellow Brick Road: A Manager's Guide to Implementing Value Creation in Your Organization. (May 2015) - Davidow, Moshe
The topic of value creation has become of utmost importance over the last few years; however, most managers have still not implemented it in their organizations. One reason for the delay is the lack of a blueprint as to how to do it, and what it entails. This article seeks to remedy that problem by laying out the steps for the creation of the Chief Customer Feedback Officer (CCFO), the nine different functions his office is entrusted with, and how they create value for the organization by providing a customer compass for the strategic direction of the organization. Some of the nine functions currently exist in the organization but are out of place and cannot influence the strategic direction of the organization. It is only by implementing all nine functions with the backing of top management that an organization can successfully become customer-centric, creating value for all of its stakeholders.